2003
DOI: 10.1002/j.2161-1912.2003.tb00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Attitudes of Asian International Students Toward Seeking Psychological Help

Abstract: Relationships between acculturation and attitudes toward psychological help seeking were studied with 170 Asian international students. Results showed a significant relationship between levels of acculturation and attitudes toward seeking professional psychological help. Significant correlations were found between students' levels of acculturation and stigma tolerance and confidence in mental health practitioners.La relacion entre la aculturacion y las actitudes hacia la busqueda de ayuda psicologica se estudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
159
10
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(180 citation statements)
references
References 36 publications
8
159
10
3
Order By: Relevance
“…Russell, Thomson, and Rosenthal (2008) conducted a large study investigating the use of health and counselling services by 979 international students at an Australian university. Overall, the international students rated the services positively, which is in contrast to prior research (e.g., Kilinc & Granello, 2003; W. M. L. Lee & Mixson, 1995;N. Zhang & Dixon, 2003).…”
Section: Underutilisation Of Student Counselling Servicescontrasting
confidence: 99%
“…Russell, Thomson, and Rosenthal (2008) conducted a large study investigating the use of health and counselling services by 979 international students at an Australian university. Overall, the international students rated the services positively, which is in contrast to prior research (e.g., Kilinc & Granello, 2003; W. M. L. Lee & Mixson, 1995;N. Zhang & Dixon, 2003).…”
Section: Underutilisation Of Student Counselling Servicescontrasting
confidence: 99%
“…The results for attitude toward seeking professional psychological help among Asian international students appears to counter previous thinking and findings that Asian Americans and Asian international students generally underutilize mental health services because of incompatible values between Asians and therapeutic processes (Zhang & Dixon, 2003). It is worth noting that Zhang (1998) compared four groups of students based on country of origin (i.e., China, Japan, Korea, and others) and the majority of the respondents came from the Far East region.…”
Section: Discussion Of Resultscontrasting
confidence: 84%
“…Their underutilization of help may be due to their experiences, values, and assumptions. It is suggested that culture plays a role in attitudes toward seeking professional psychological help (Zhang & Dixon, 2003).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Several more recent studies also replicated the findings of Atkinson and Gim. Tata and Leong (1994) and Zhang and Dixon (2003) surveyed 219 Chinese Americans college students and 170 Asian International students respectively. They both found a positive relation between level of acculturation and attitude toward seeking professional psychological help.…”
Section: Attitudes Toward Seeking Psychological Servicesmentioning
confidence: 99%